Extracts of a marxist ontology of law in Roberto Lyra Filho - Soares, Moisés Alves (2017)
The work of Roberto Lyra Filho consists of a constant track of the essence of the right in the historical and social reality and points  to concrete realization of justice. The carioca’s jurist in the development of this theoretical synthesis walks toward a marxist ontology of law - fundamental point and strangely little emphasized by their interpreters - supported the contributions of three giants of marxist thought: György Lukács, with his Ontology of Social Being, Ernst Bloch with its The Principle of Hope; and finally, the Ontology of Praxis present in Prison Notebooks. The “uses” that Lyra Filho makes of extracts of these Marxist theories combined with Boaventura’s legal pluralism in its dialectical ontology of law are rich in interpretive possibilities, which will be focused in this study.